Clinical characteristics and outcome of COVID-19 patients with Parkinson’s disease: a hospital-based case–control study in Shanghai, China - Wu, Li; Shen, Jun; Jiang, Yuhan; Shen, Xiaolei; Wang, Ping; Nie, Xin; Kang, Wenyan; Liu, Jianren; Chen, Wei (Frontiers in Aging Neuroscience, 2023)
Background: Clinical manifestations of Parkinson's disease (PD) after Corona Virus Disease 2019(COVID-19) infection are poorly investigated. Objective: We aimed to explore the clinical features and outcomes of hospitalized PD patients with COVID-19. Methods: A total of 48 PD patients and 96 age- and sex- matched non-PD patients were included. Demographics, clinical characteristics and outcomes were compared between two groups. Results: PD patients with COVID-19 were elderly (76.69±9.21 years) with advanced stage (H-Y stage 3-5 as 65.3%). They had less clinical symptoms(nasal obstruction, etc), severe/critical COVID-19 clinical classification (22.9 vs. 1.0%, p<0.001), receiving oxygen(29.2 vs. 11.5%, p=0.011), antibiotics (39.6 vs. 21.9%, p=0.031) therapies, as well as longer hospitalization duration (11.39 vs. 8.32, p=0.001) and higher mortality (8.3% vs. 1.0%, p=0.001) relative to those without PD. Laboratory results showed that the PD group had higher white blood cell counts (6.29 vs. 5.16*10^9, p=0.001), neutrophil-to-lymphocyte ratio (3.14 vs. 2.11, p<0.001) and C-reactive protein level (12.34 vs. 3.19, p<0.001). Conclusion: PD patients with COVID-19 have insidious clinical manifestation, elevated proinflammatory markers and are prone to the development of severe/critical condition, contributing to a relatively poor prognosis. Early identification and active treatment of COVID-19 are pivotal to advanced PD patients during the pandemic.